Towards a reinterpretation of article VI of the Preliminary Title of the Civil Code: in search of the parameters of the “standing to sue” - Ariano Deho, Eugenia (2020)
This paper analyses Article VI of the Preliminary Title of the Civil Code for the purpose of determining its current usefulness. For this purpose it goes back to the origins and sense of the French maxim “interest is the measure of actions”, its reception in the Italian Procedural Code of 1865 and successive conceptual developments, going so far as to argue that article VI analyzed contains the parameters (legitimate, economic or moral usefulness) needed to establish the existence of what the Civil Procedural Code calls “interés para obrar”, that is, if the requested (or a substantive defense) is appropriate to receive a substantive decision.